The School of Geographic Sciences as a Protagonist in Land-Use Planning: Experience from PROGOT - Calderón Ramírez, Guillermo (2024)
Land-use management and planning aim to contribute to territorial development, where various components converge from social, economic, environmental, and technological perspectives. The Program for the Promotion of Land Management and Planning (PROGOT) seeks to create platforms for sharing experiences in land-use planning processes, generating synergies through collaborative discussions among the involved stakeholders.